Heart transplantation as salvage treatment of intractable infective endocarditis. (April 2015) - Aymami, Marie; Revest, Matthieu; Piau, Caroline; Chabanne, Céline; Le Gall, François; Lelong, Bernard; Verhoye, Jean-Philippe; Michelet, Christian; Tattevin, Pierre; Flécher, Erwan
Abstract: This study reports six consecutive patients who underwent heart transplantation as salvage treatment for endocarditis (Duke criteria) with extensive perivalvular lesions and end-stage heart failure. The median age was 45 years (range, 24 to 64), and the aortic valve was affected in all patients. Pathogens were Staphylococcus aureus (n = 2), Streptococcus pneumoniae (n = 2), Streptococcus agalactiae (n = 1), or not documented (n = 1). All patients survived, with no relapse, after a median follow-up of 24.5 months. The 10 patients with heart transplantation for endocarditis previously reported also survived (median follow-up, 27.5 months). Heart transplantation may be considered as salvage treatment in selected patients with intractable infective endocarditis.